"Live High - Train Low" altitude training for endurance performance - Smart, N. A. (Journal of Athletic Enhancement, 2012)
Coaches and athletes alike are constantly striving for training strategies to provide an advantage over their competitors. Altitude training is an integral part of many endurance athlete`s preparation for competition and a common approach to this conditioning strategy is `live high train low` (LHTL) where as the description implies athletes live at altitude to stimulate physiological adaptation but train at sea level so exercise intensity can be maintained and de-conditioning avoided. LHTL can be achieved naturally or artificially which can be grouped into three distinct categories (Figure 1) [1] the artificial long continuous approach includes studies in which participants are exposed to simulated moderate altitude (generally defined as 1,500 m-2,500 m) for 8 to 18 hours per day. The artificial short continuous approach includes studies in which participants are exposed to simulated moderate-high altitude (generally defined as 2,500 m-5,300 m) for 1.5 to 5 hours per day. The artificial brief intermittent approach includes studies in which participants are exposed to simulated high altitude (generally defined as 5,300 m-8,848 m) for less than 1.5 hours per day. The aim of this editorial is to combine information from a recent meta-analysis and an associated editorial to provide guidance with training regime design for future LHTL work